2018
DOI: 10.3389/fimmu.2018.02636
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Adaptations of Memory and Tissue-Resident Gamma Delta T Cells

Abstract: Epithelial and mucosal barriers are critical interfaces physically separating the body from the outside environment and are the tissues most exposed to microorganisms and potential inflammatory agents. The integrity of these tissues requires fine tuning of the local immune system to enable the efficient elimination of invasive pathogens while simultaneously preserving a beneficial relationship with commensal organisms and preventing autoimmunity. Although they only represent a small fraction of circulating and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 282 publications
3
107
0
Order By: Relevance
“…Gamma delta (cd) T cells are thymus-derived unconventional T cells that display innate as well as adaptive immunological features. 42 While cd T cells represent only a small fraction of T cells in the circulation or lymphoid tissues, they form a substantial tissue-resident population at epithelial and mucosal barrier sites and are therefore likely influenced by the intestinal microbiota. Some tissues contain highly restricted or specialized cd T-cell populations, such as Vc5 + T cells, that are exclusively found in the intestinal epithelium.…”
Section: Impact Of the Microbiota On Memory-like CD T Cellsmentioning
confidence: 99%
“…Gamma delta (cd) T cells are thymus-derived unconventional T cells that display innate as well as adaptive immunological features. 42 While cd T cells represent only a small fraction of T cells in the circulation or lymphoid tissues, they form a substantial tissue-resident population at epithelial and mucosal barrier sites and are therefore likely influenced by the intestinal microbiota. Some tissues contain highly restricted or specialized cd T-cell populations, such as Vc5 + T cells, that are exclusively found in the intestinal epithelium.…”
Section: Impact Of the Microbiota On Memory-like CD T Cellsmentioning
confidence: 99%
“…DETC and γδ IELs reside in close proximity to microorganisms in the skin and intestine, respectively, and function in the control of both host microbiota and invading bacteria [106]. While the overall impact on γδ T cell-mediated barrier maintenance is unknown, studies in germ-free and antibiotic-treated mice have suggested that the microbiota can influence the functions of γδ T cells in these tissues, and the presence of commensals is required for the normal distribution and migration of γδ IELs [106,107]. γδ IELs have been described as having an "activated but resting" phenotype in which cytotoxic genes are expressed at steady state alongside the expression of inhibitory receptors [108,109], a combination that may allow a rapid response rate while maintaining control over effector function at homeostasis.…”
Section: γδ Iel Functions In Homeostasis and Epithelial Damage Repairmentioning
confidence: 99%
“…Mouse γδ subsets have been suggested to have an innate-like biology. However, there is evidence in multiple models which suggests that IL-17 producing Vγ6+ T cells and Vγ4+ T cells (γδ17 T cells) undergo adaptive-like differentiation through naïve precursors into mature γδ17 T cells in peripheral lymphoid organs [108]. In terms of aging, Chen et al demonstrated that aging alters TCRδ chain usage and the clonal structure of γδ T cells.…”
Section: In Micementioning
confidence: 99%